Low protein diet score: a novel diet quality index and predictor of disease progression in patients with chronic kidney disease - Rouhani, Mohammad Hossein; Mortazavi Najafabadi, Mojgan; Azadbakht, Leila (Progress in Nutrition, 2018)
Background and Aim: Patients with chronic kidney disease (CKD) have been recommended to consume a low protein diet. However, there is no specific index for evaluating amounts of dietary protein and CKD progression in these patients. The objective of this study was to define a low protein diet score (LPDS) as a predictor of CKD progression and an index of diet quality in patients with CKD. Methods: For this cross-sectional study, two hundred twenty seven eligible subjects with CKD (stage 3 and 4) were selected. We used a validated food frequency questionnaire to assess dietary intake of patients. LPDS was defined based on the 3 cut of points: >2 gr/kg (score=1), 1.01-2 gr/kg (score=2) and ≤ 1 gr/kg (score=3). Renal function (i.e., blood urea nitrogen and serum creatinine) and cardiometabolic variables (i.e., low density lipoprotein, triglyceride, total cholesterol, fasting blood sugar and high sensitivity C-reactive protein) were measured by biochemical assessment. As dietary intakes of sodium, potassium, phosphorus, saturated fatty acid and cholesterol are important, we used intake of these nutrients to assess diet quality. Results: Patients who received higher scores, had better diet quality because they consumed lower amounts of phosphorus, potassium, saturated fatty acid and cholesterol (P<0.01 for all). Biochemical assessments showed that in comparison with the bottom LPDS, a marginally significant lower blood urea nitrogen was observed among subjects with higher scores (P=0.06). We did not observe any significant difference in other biochemical variables across the defined LPDS. After adjusting for all confounders, a significant decreasing trend for risk of CKD progression was revealed across LPDS (P for trend=0.04). Conclusion: The results of the present study showed that higher LPDS was associated with favorable nutrients intake (lower intakes of sodium, potassium, phosphorus, cholesterol and saturated fatty acid) among patients with CKD. Moreover, subjects who received higher LPDS had a marginally significant lower BUN. Also, we observed that LPDS was inversely related to the risk of being in the higher stage of CKD after adjusting for potential confounders. Therefore, it was a predictor of CKD progression.